Irrigation, a potential tool for insect pest management in horticultural crops — a review (Current Horticulture, 2024)
Irrigation, probably more than any other single factor, has a greater role to enhance the production and productivity of horticultural crops. Different methods of irrigation systems are being followed for various horticultural crops. Apart from soddening the crops, irrigation can also play a pivotal role in insect pest management in so many horticultural crops. A light irrigation minimizes the termite infestation. The drip irrigation in perennial orchard helps maintain lower level of insect pests compared to flood irrigation; whereas drip irrigation maintains the incidence of tomato fruit borer to lower level in field instead of sprinkler irrigation. The paper illustrates this theory by reference to illustrates and discusses the ways in which insect pests menace can be minimized in horticultural crops.
Keywords: Irrigation; Horticultural crops; Insect pests management; Drip irrigation; Sprinkler irrigation